Knowledge, Attitude and Perception (KAP) Regarding Halal Pharmaceuticals among General Public in Penang State of Malaysia - Saleha Sadeeqa; Azmi Sarrif; Imran Masood; Fahad Saleem; Muhammad Atif (International Journal of Public Health Science (IJPHS), 2013)
This study was designed as questionnaire based a cross-sectional analysis and aimed to assess knowledge, attitude & perception regarding Halal pharmaceuticals, among general public of Penang, Malaysia. A total of 458 Muslims, having age 18 years or above and able to read and understand Malay language was included. Study settings included different shopping malls, bus stations, food courts and markets of Penang state. Data was collected through trained data collectors. Results revealed that public has a good and positive towards Halal pharmaceuticals. Mean knowledge score was 6.41 ± 1.35 (out of 9), while mean attitude and perception score out of maximum possible score of 35 each were 25.86±4.03 and 30.71±4.47 respectively. Mean overall knowledge, attitude and perception (KAP) score out of maximum possible score of 79 was found to be 62.74±7.65. Positive yet weak significant correlation was reported between knowledge and attitude (r=0.099, p=0.035) and attitude and perception (r=0.156, p=0.001). However, the significance between knowledge and perception was positive and moderate in relationship (r=.440, p=.036). The study concluded that better knowledge of Halal pharmaceuticals is associated positive perceptions and behaviours.DOI: http://dx.doi.org/10.11591/ijphs.v2i4.4226